Potential of traditional medicines in alleviating COVID-19 symptoms - Chatatikun, Moragot; Indo, Hiroko P.; Imai, Motoki; Kawakami, Fumitaka; Kubo, Makoto; Kitagawa, Yoshimasa; Ichikawa, Hiroshi; Udomwech, Lunla; Phongphithakchai, Atthaphong; Sarakul, Orawan; Sukati, Suriyan; Somsak, Voravuth; et al. (Frontiers in Pharmacology, 2024)
This review discusses the prevention and treatment of coronavirus disease 2019 (COVID-19) caused by infection with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Mutations in its spike glycoprotein have driven the emergence of variants with high transmissibility and immune escape capabilities. Some antiviral drugs are ineffective against the BA.2 subvariant at the authorized dose. Recently, 150 natural metabolites have been identified as potential candidates for development of new anti-COVID-19 drugs with higher efficacy and lower toxicity than those of existing therapeutic agents. Botanical drug-derived bioactive molecules have shown promise in dampening the COVID-19 cytokine storm and thus preventing pulmonary fibrosis, as they exert a strong binding affinity for viral proteins and inhibit their activity. The Health Ministry of Thailand has approved Andrographis paniculata (Jap. Senshinren) extracts to treat COVID-19. In China, over 85% of patients infected with SARS-CoV-2 receive treatments based on traditional Chinese medicine. A comprehensive map of the stages and pathogenetic mechanisms related to the disease and effective natural products to treat and prevent COVID-19 are presented. Approximately 10% of patients with COVID-19 are affected by long COVID, and COVID-19 infection impairs mitochondrial DNA. As the number of agents to treat COVID-19 is limited, adjuvant botanical drug treatments including vitamin C and E supplementation may reduce COVID-19 symptoms and inhibit progression to long COVID.